2020
DOI: 10.3390/ijerph17165677
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Participation Patterns and Impact of Environment in Preschool Children with ASD

Abstract: Participation in everyday activities at home and in the community is essential for children’s development and well-being. Limited information exists about participation patterns of preschool children with autism spectrum disorder (ASD). This study examines these participation patterns in both the home and community, and the extent to which environmental factors and social communication abilities are associated with participation. Fifty-four parents of preschool-aged children with ASD completed the Participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 52 publications
4
7
1
Order By: Relevance
“…Our findings also indicated that children with developmental disability generally have lower rates of participation in community settings when compared to other settings, which was also found in other studies (Di Marino et al, 2018; Khalifa et al, 2020; Khetani, 2015). Interestingly, although the number and frequency of activities performed were the lowest in the community, parents indicated the lowest need for change in this setting.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings also indicated that children with developmental disability generally have lower rates of participation in community settings when compared to other settings, which was also found in other studies (Di Marino et al, 2018; Khalifa et al, 2020; Khetani, 2015). Interestingly, although the number and frequency of activities performed were the lowest in the community, parents indicated the lowest need for change in this setting.…”
Section: Discussionsupporting
confidence: 89%
“…Lithuanian children with developmental disability quite rarely (on average from once each week to several times in the last month) participated in household chores, such as meal preparation, taking care of family members, and laundry handling. Similar data can be found in the literature on home participation of preschool and school-aged children with different types of disability in different countries (Bakaniene and Prasauskiene, 2020; Di Marino et al, 2018; Khalifa et al, 2020; Larson and Verma, 1999). We do not have data on the participation of typically developing Lithuanian children household chores and in general, therefore we cannot conclude whether the participation of children with disability in household chores is lower or not.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations